(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article reveals the main points of organizing work in small groups, the need to organize individual work, simultaneously with the organization of general work, methods for conducting interactive classes, as well as depending on the level of complexity of tasks.